A founder COL4A3 pathogenic variant resulting in Alport syndrome and thin basement membrane disease: a case report series - Tkemaladze, Tinatin; Bregvadze, Kakha; Kvaratskhelia, Eka; Abzianidze, Elene; Davitaia, Tinatin (Frontiers in Medicine, 2023)
Alport syndrome is a rare genetic condition characterized by kidney disease, hearing impairment, and ocular abnormalities. It exhibits various inheritance patterns involving pathogenic variants in COL4A3, COL4A4, and COL4A5 genes. The phenotypes can range from isolated haematuria with a nonprogressive or very slowly progressive course to progressive kidney disease with extrarenal abnormalities. Timely diagnosis of Alport syndrome facilitates the early and effective implementation of treatment, as well as genetic counseling. Here, we report the COL4A3 c.765G>A, p.((=)) mutation in three ethnically Azerbaijani, apparently unrelated, consanguineous families from the village of Algeti in the Marneuli region of Georgia. We speculate that this variant could represent a founder mutation within this population and recommend offering genetic testing to Algeti village residents with persistent hematuria.